(untitled) (Journal of the College of Basic Education, 2022)
The football game, which has occupied a distinguished position in the world, like other sports, is still gaining popularity and public admiration among sports followers, as its practice depends on teamwork, so researchers in the sciences of physical education have given this game great attention, and perhaps this is the advancement of the level of the game Increasing the demand for its practice is the conclusion of serious scientific planning in all the requirements of the game in terms of developing its missions, acquiring basic information related to it, understanding the correct methods of practicing it and learning methods, and the availability of scientific resources and competent educational staff through the use and development of scientific research.